A blessed journey / Rafidah Abas and Johanudin lahap@Wahab - Abas, Rafidah; Lahap@Wahab, Johanudin (Faculty of Hotel & Tourism Management, UiTM Pulau Pinang, 2019)
Worldwide Tourism was organized by PHM111 2A1/2 on the 23rd of November, 2018 at Laman Perdana. It was a partial requirement for HTT251- Meeting, Incentives, Convention and Events (MICE) where students were required to organize MICE related events. In addition, the objectives were to expose the students to the essential elements in event planning and organization as well as to provide a platform for the audience and participants to gain international cultural experience. The event showcased numerous activities such as international cultural fair, quiz, lucky draw, photo booth, preloved item sale and seminar. The revenue from the preloved item sale and collection from the donation box was channeled to the beneficiary, Rumah Permata Kasih, Taman Seri Mengkuang. The engagement of entrepreneurship community service elements was part of the organizer’s support toward UiTM’s mission in enhancing knowledge and improving Bumiputeras’ expertise in all areas. "A Blessed Journey” was the event’s hallmark where participants could interact actively with Mohammad Kareef Daniel Abdullah or Mat Dan, a celebrity famous for his Terengganu accent who casts reality TV shows, telemovies and sitcoms. The seminar had given the audience the chance to learn the nitty gritty of cultural interaction as Mat Dan shared his life and travel experiences since he left his hometown, Bristol, England and came to Malaysia in 2009. His love for Malaysian culture had brought him here for good where he reverted to Islam and settled down with a Malaysian.